Optimization parameters system maintenance transport aircraft - Ліннік, І.І. (Proceedings of National Aviation University (archive), 2006)
The algorithm of unconditional and conditional optimization Markov models of maintenance systems of transport airplanes of their programs of technical operation used at improvement is considered.